Do eco-innovations need specific regional characteristics? An econometric analysis for Germany - Jens Horbach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The theoretical and empirical innovation literature stresses the importance of regional fac-tors and locational conditions for location choice of firms and their innovation success. Innovation activities are not equally distributed in space because agglomeration effects and specific regional infrastructures may promote innovation success. Concerning environmentally oriented innovations, the so-called eco-innovations, there is a widespread empirical literature analyzing their determinants but - because of the lack of adequate data - the inclusion of regional and locational factors has been neglected. This paper tries to close this gap by using the establishment panel of the German Institute for Employment Research in Nuremberg combined with data at the regional level. To explore specific regional determinants of eco-innovations compared to other innovations including variables at the firm and the regional level, a two-level mixed effects logistic regression has been applied. Our econometric results show that external knowledge sources such as the regional proximity to research centers and universities are more important for eco-innovations compared to other innovations. Eco-innovations seem to be a chance for under-developed, disadvantaged regions because especially regions characterized by a high unemployment rate are more likely to adopt eco-innovations. Furthermore, eco-innovations need more effort concerning R&D inputs, further education measures within a firm and the qualifi-cation of the personnel.
Keywords: Q55; R11; C25; 330